Labor Relations in the Aviation and Aerospace Industries - Kaps, Robert W., 1943- (Book collections on Project MUSE., 2012)
In this textbook designed for courses on aviation labor relations, the authors-experts with many years of experience in these sectors-examine and evaluate the labor process for all aspects of the aviation and aerospace industries, including aerospace manufacturing, airlines, general aviation, federal and state administrative agencies, and public airports. Divided into three parts-Public Policy and Labor Law; Principles, Practices and Procedures in Collective Bargaining and Dispute Resolution; and the Changing Labor Relations Environment-the book provides an overview of the industries and the development of US labor law and policy, then explores the statutory, regulatory, and case laws applicable to each industry segment before concluding with an examination of current and developing issues and trends. The authors present the evolution of aviation and aerospace labor laws, going as far back as the early nineteenth century to lay the historical foundation, and cover the development and main features of the principal statutes governing labor relations in the United States today, the Railway Labor Act, the National Labor Relations Act, and the Civil Service Reform Act. They also investigate the growth of the industries and their impact on labor relations, as well as the current issues and challenges facing management and labor in each segment of this dynamic, sometimes volatile, business and their implications for collective bargaining. Twenty case studies not only illuminate practical applications of such fundamental concepts as unfair labor practices and unions' duty of fair representation but also enliven the subject, preparing the reader to use the concepts in real-world decision making. A study guide with review questions, online assignments, supplemental readings, and exercises is available for students. For those teachers using the textbook in their courses, there is an instructor's manual with additional resources for developing courses in the classroom, online, or by blended learning, as well as a variety of assignments and materials to enhance and vary the mock negotiation exercise. A revision and expansion of Robert W. Kaps's Air Transport Labor Relations, this outstanding new volume provides students and teachers with valuable information and perspectives on industries that are highly dependent on technologically skilled labor. Labor Relations in the Aviation and Aerospace Industries offers a sweeping and thorough treatment of labor relations, public policy, law, and practice and is the definitive work on the labor process in the aviation and aerospace sectors.